ECONOMIC ANALYSIS AND FACTORS INFLUENCING CUSTOMER SATISFACTION AND ELECTRICITY PURCHASE DECISIONS IN A CASE STUDY AT PT. PLN IN INDONESIA - Rio Afrianda; Veithzal Rivai Zainal, Indra Siswanti, Lenny Christina Nawangsari (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research aims to explore the factors that impact customer satisfaction and purchasing decisions among PT PLN (Persero) electricity consumers across Indonesia. A sample of 70 consumers was surveyed using a questionnaire to collect data. The analysis utilized linear regression through SPSS Statistics, considering variables such as product, price, distribution channel, promotion, and service quality as independent, intervening, and dependent factors. The study uncovered several significant findings: firstly, both price and service quality play crucial roles in influencing customer satisfaction. Secondly, distribution channels and customer satisfaction notably affect PT PLN (Persero)'s electricity purchasing decisions in Indonesia. Thirdly, collectively, products, prices, distribution channels, promotions, and service quality contribute to customer satisfaction, consequently impacting PT PLN (Persero)'s electricity purchasing decisions across these regions. Particularly noteworthy is the introduction of a novel model depicting the relationship between promotional activities promoting electricity conservation, customer satisfaction, and purchasing decisions. The implications of this research are expected to aid electricity management and industry professionals in enhancing customer satisfaction and guiding PT PLN (Persero)'s electricity purchasing decisions in Indonesia. Furthermore, it could serve as a valuable resource for future research endeavors and corporate decision-making processes.